Penambahan Bovine Serum Albumin pada Beltsville Thawing Solution Dapat Mempertahankan Kualitas Semen Babi yang Disimpan pada 15°C (ADDITION OF BOVINE SERUM ALBUMIN TO BELTSVILLE THAWING SOLUTION COULD MAINTAIN QUALITY OF PIG SEMEN STORED AT 15OC) - Bebas, Wayan; Gorda, Wayan (Jurnal Veteriner; Vol 20 No 3 (2019), 2019)
This study aims to maintain the quality of pig semen for longer during storage at 15oC, in an effort to support artificial insemination programs with the addition of Bovine Serum albumin (BSA) to diluent Beltsville Thawing Solution (BTS). This study uses a completely randomized design with five treatment groups, each To = semen was diluted with BTS without the addition of BSA ; T1 = with the addition of 5 mg BSA/mL diluent; T2 = with the addition of 10 mg BSA/mL diluent; T3 = with the addition of 15 mg BSA/mL diluent; T4 = with the addition of 20 mg BSA/mL diluent. Each treatment was repeated five times so that the number of samples used was twenty-five. The diluted cement is stored at 15oC for 72 hours then observing the quality of cement includes: progressive motility, dead spermatozoa, abnormalities, and intact plasma membranes. The data obtained were analyzed by analysis of variance, if there were differences followed by Duncan’s test. The results showed, addition of BSA concentration of 10 mg/mL and 15 mg/mL of diluent gives the same effect on the quality of cement during storage and significantly better (p <0.05) when compared to the addition of 0 mg/mL, 5 mg/mL and 20 mg/mL diluents. It can be concluded, the addition of BSA 10 mg/mL BTS diluents can maintain the most optimal quality of pig semen against progressive motility, dead spermatozoa, abnormalities and intact plasma membranes.